Umbilical Cord Abnormalities and Stillbirth. Issue 4 (December 2020) - Hammad, I.A.; Blue, N.R.; Allshouse, A.A.; Silver, R.M.; Gibbins, K.J.; Page, J.M.; Goldenberg, R.L.; Reddy, U.M.; Saade, G.R.; Dudley, D.J.; Thorsten, V.R.; Conway, D.L.; et al.
Abstract : ( Obstet Gynecol . 2020;135:644–652). Colloquially known as "cord accidents, " stillbirths due to umbilical cord abnormalities occur when blood supply through the umbilical cord is disrupted severely enough to cause fetal death. Unfortunately, the reported rates of umbilical cord abnormalities associated with stillbirth range widely from 2.5% to 30%, and the diagnostic criteria for these abnormalities have not been clearly defined. This study aimed to rigorously characterize stillbirths associated with cord abnormalities, and further examine the maternal and clinical factors associated with these perinatal losses.